Calculadoras, Computadores e Internet em Educação Matemática: dezoito anos de pesquisa - Maltempi, Marcus Vinicius [UNESP]; Javaroni, Sueli Liberatti [UNESP]; De Carvalho Borba, Marcelo [UNESP] (My University, 2011)
In this paper, we present GPIMEM, a group that has been developing research in Mathematics Education related to computers and other media since 1993 to understand how mathematical knowledge can be produced with these technological resources, in face-to-face as well as online distance education. Members of the group dialogue with different fields of knowledge such as philosophy, history, psychology, anthropology, sociology, arts and technology, among others, to inform their research. The research addresses various topics relevant to Mathematics Education, including methodological and epistemological aspects of teaching and learning, of mathematical modeling and teacher education, always within a qualitative research perspective. We begin with the historical presentation of the group, revealing its dynamics and organization of work, followed by reflections on qualitative research methodology and description of research conducted over the past five years. Finally, we present a synthesis of the theories developed by the group and expectations for the future.
Calculators, computers and internet in mathematics education: Eighteen years of research
Keywords: Information and communication technologies; Mathematics education; Online distance education; Qualitative research; Research group